EFFECT OF SERVICE QUALITY AND FACILITIES ON COMMUTERLINE TRAIN USER SATISFACTION: A CASE OF INDONESIA - Aswanti Setyawati; Husni Hasan (ABNUS Publisher, 2021)
The effect of service quality and facilities on user satisfaction of JABODETABEK Commuter Line Train. The purpose of this study was to see how the influence of service quality and facilities on user satisfaction of Jabodetabek commuter line trains. The method used in this research is quantitative research which is descriptive and verification in nature. Data collection techniques using questionnaires, observation and literature study. While the data analysis method used in this research is validity test, reliability test, path analysis, t test and F test using SPSS.23.0. The sampling technique used was non-probability sampling, purposive sampling type. The number of users sampled is a population of 336,045 passengers with a 5% MOE at a 95% confidence level based on the Isaac & Michael formula is S = 348 samples. According to analysis carried out it can be concluded quality of service effect amounted to 38.00% on user satisfaction Commuter Line, influential facilities for 40.30% of the Commuter Line user satisfaction and jointly quality of service and facility has an influence of 78.30% on Commuter Line Train user satisfaction. Based on the results of this study, the steps that need to be taken by the management of PT. KAI is to make efforts to further improve the quality of Commuter Line Train user satisfaction through improving the quality of service (Service Quality) and facilities (Facility / infrastructure).